Reduction Of Criminal Penalties for Corruption Criminal Acts as Regulated in Law No. 1 of 2023 Concerning the Criminal Code - Zahrotus Suroya; Pudji Astuti (NOVUM : JURNAL HUKUM, 2024)
The crime of corruption is an extraordinary crime, which should be able to deter the perpetrators from committing the crime again. However, the new rules made in Law No.1 of 2023 concerning the Criminal Code have lightened the prison sanctions and fines for perpetrators of corruption when compared to Law No.31 of 1999 concerning corruption. The purpose of this research is to find out what is the basis for the rules of corruption offenses to be included in the National Criminal Code and to find out the basis for reducing the sentences for corruption offenses in the National Criminal Code. So that problems related to the reduction of criminal sanctions for corruption motivate the author to conduct research using normative legal research methods with a statutory approach, conceptual approach, and historical approach. The data collected is then analyzed prescriptively. The result of the research is that corruption can be included in the National Criminal Code through the principle of codification and it can be seen that the reduction of punishment for corruption offenders is based on the politics of criminal law, individualization of punishment, and punishment. However, this is not in accordance with the existing facts considering that this corruption case is detrimental not only to the state but also to society.